PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW PADA MATERI SUHU DAN PENGUKURAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA. - Jamiluddin Sampe, Yulia Nurpadila; Marianus, Marianus; Rende, Jeane C. (Charm Sains: Jurnal Pendidikan Fisika, 2023)
The jigsaw type cooperative learning model is an example of a learning model that can be used by teachers in the teaching and learning process to improve student learning outcomes. The purpose of this research is to improve the process and learning outcomes of class XI IPA senior high school students on the topic of physics, temperature and heat by using the Jigsaw learning model. The method used in this research is experimental research using a one group pre-test-post-test design. This research was conducted through three stages. The first stage is to provide a pre-test to measure students' initial abilities. The second stage is giving treatment through a jigsaw cooperative learning model and the third stage is giving a post-test as a learning evaluation. The research subjects were high school students in class XI IPA at SMAN 2 Tondano 2022/2023. After the research data were obtained, they were statistically processed using SPSS 22.0 for windows. The average pre-test result was 5.32 and the post-test result was 85.21. Obtaining N-Gain scores from each student, there were 18 students in the high N-Gain category and 1 student in the medium N-Gain category, the total number of students who took part in the pre-test and post-test were 19 students. The results of this study indicate that by applying the jigsaw cooperative learning model to the physics topic of temperature and its measurement, student learning outcomes have increased